Chordoid Glioma with Psychosis: Case Report - Estronza, Samuel; Saavedra, Fanor M.; De Jesus, Orlando; Pastrana, Emil A. (Puerto Rico Health Sciences Journal, 2018)
Objective: A rare, low-grade tumor found in the hypothalamus and anterior third ventricle, a chordoid glioma presents a challenge to neurosurgeons: Its successful resection is complicated by its inconvenient location. Case Description: A 42-year-old male patient presented with a 1-year history of major depressive disorder, with psychotic features associated with generalized tonic–clonic seizures. Brain magnetic resonance imaging (MRI) with contrast revealed a suprasellar mass extending into the third ventricle To resect the lesion, an interhemispheric transcallosal transventricular subfornical approach was used. Pathology revealed a chordoid glioma. The patient had a complicated post-operative period that included the development of neurogenic diabetes insipidus, followed by intractable hyponatremia and death (caused by malignant brain edema). Conclusions: A chordoid glioma is a rare neoplasm that, in 2000, was incorporated into the World Health Organization (WHO) classification of central nervous system tumors. Due to its rarity, it is seldom considered in the differential diagnosis of suprasellar masses. Moreover, its unusual presentation and difficult location present a challenge for surgical and medical management.